A revision of the genera Anilaroides Théry, 1934, stat. nov. and Tetragonoschema Thomson, 1857 (Coleoptera: Buprestidae: Buprestinae: Anthaxiini) - Bílý, Svatopluk (Zootaxa, 2012)
A taxonomic revision of the genera Tetragonoschema Thomson, 1857 and Anilaroides Théry, 1934, stat. nov., with the descriptions of the subgenus Patagoschema subgen. nov. and two new species: Tetragonoschema (T.) barriesi sp. nov. (Paraguay) and T. (P.) cobosi sp. nov. (Argentina). Representatives of all the included species and their male genitalia are illustrated and all species are keyed. Taxonomic history of the genera is given and all available data concerning their bionomy are compiled.